Pest control with fewer chemicals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Alois Chimoga of the Cotton Research Institute in Zimbabwe on crop hygiene and correct use of pesticides.